Ideal-Normative and Socio-Historical Approaches to Gender Equality Verses: A Study of Riffat Hassan's Thought - Mia Nurmala; Umi Sumbulah; Yayan Nurbayan (Millah: Journal of Religious Studies, 2023)
Gender equality issues never stop being discussed and always attract attention. This is driven by the many inequalities experienced by women from ancient times until now. Even though gender equality is increasingly being echoed, the position of women is always affected and biased by patriarchal culture. Often women are made second. Islam itself provides space for gender equality. This study aims to discuss Riffat Hassan's thoughts on realizing gender equality in the Islamic view. This study also uses a qualitative descriptive method with a narrative analysis approach. The data was collected by documenting various sources related to Hassan and her thoughts and was analyzed using interactive qualitative analysis. The results show that there are two approaches used by Riffat Hassan in interpreting the verses of the Koran: the ideal-normative and socio-historical approaches. In her view, the basis of a contested patriarchal culture is related to 1) God first created men, not women; women are believed to have been created from the ribs of men. Therefore, women are derivative and ontologically secondary; 2) women, not men, are the primary agents for human fall from heaven; and 3) women are not only created by men but also for men, so the existence of women is only a tool and has no fundamental meaning.